41.5k views
4 votes
Prove that: (1 + cos A)^2 - (1 - cos A)^2/
sin^2 A=
4cosec A. cotA​

User Giridhar
by
4.9k points

1 Answer

3 votes

Answer:

see explanation

Explanation:

Using the trigonometric identities

cosec x =
(1)/(sinx) , cot x =
(cosx)/(sinx)

Consider the left side


((1+cosA)^2-(1-cosA)^2)/(sin^2A) ← expand and simplify numerator

=
(1+2cosA+cos^2A-(1-2cosA+cos^2A)/(sin^2A)

=
(1+2cosA+cos^2A-1+2cosA-cos^2A)/(sin^2A)

=
(4cosA)/(sin^2A)

= 4 ×
(1)/(sinA) ×
(cosA)/(sinA)

= 4cosecAcotA

= right side, thus proven

User John Coleman
by
5.3k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.